2001
DOI: 10.1016/s0886-3350(01)00900-2
|View full text |Cite
|
Sign up to set email alerts
|

Relation between corneal thickness and intraocular pressure measurement by noncontact and applanation tonometry

Abstract: The reliability of tonometers decreased with increasing corneal thickness, in which case higher readings were found, especially with the noncontact tonometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
4
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 18 publications
5
35
4
4
Order By: Relevance
“…Another study reported a significant intraindividual difference between the NCT (Topcon CT60) and GAT measurements in 60 glaucoma patients (120 eyes). 16 The difference was positively correlated with CCT in eyes with a corneal thickness greater than 574.5 mm. This indicates that the CCT-induced overestimation is greater with the NCT than that with the GAT in eyes with a thick cornea.…”
Section: Discussionmentioning
confidence: 87%
“…Another study reported a significant intraindividual difference between the NCT (Topcon CT60) and GAT measurements in 60 glaucoma patients (120 eyes). 16 The difference was positively correlated with CCT in eyes with a corneal thickness greater than 574.5 mm. This indicates that the CCT-induced overestimation is greater with the NCT than that with the GAT in eyes with a thick cornea.…”
Section: Discussionmentioning
confidence: 87%
“…The NCT is estimated to exhibit a deviation of 0.10 mm Hg from the GAT for every 10-µm increase in CCT. Previous studies have reported a deviation of 0.22-0.98 mm Hg for a similar change of CCT [22,23,24]. There is a significant controversy regarding the influence of CCT on IRT measurements compared to the GAT.…”
Section: Discussionmentioning
confidence: 98%
“…Whether these factors had been balanced between the cohorts were not mentioned in the parallel-designed RCTs in this meta-analysis. The Perkins applanation tonometry provides the same accuracy as GAT, while noncontact tonometry (NCT) will be less accurate [49]. These measurement errors might interfere with the validity of the results and contribute to the variety of the effects measured by different studies, although the analysis result was not biased by omitting the data measured by NCT.…”
Section: Discussionmentioning
confidence: 99%